CEO AGE AND THE DYNAMIC CAPITAL STRUCTURE EVIDENCE FROM MALAYSIA - Mei Shan, Chua; Ab Razak, Nazrul Hisyam; Md Nassir, Annuar; Yahya, Mohd Hisham (Malaysian Journal of Business and Economics (MJBE), 2020)
This paper aims to investigate the dynamic capital structure of Malaysian firms from upper echelon perspective. Specifically, we test the speed of adjustment towards the target leverage and the age of Chief Executive Officers (CEOs) as a determinant of dynamic capital structure. Utilisation of the System Generalized Method of Moments finds 33.93 of% speed of adjustment for Malaysian firms. The CEOs age is also found to be inversely related to both the optimum leverage and speed of adjustment towards the optimum leverage. As the CEOs age increases, the optimum leverage and speed of adjustment decrease. Our results are robust using the long-term leverage while controlling several firm characteristics that are known to impact the firm’s capital structure, year of effect, and industry fixed effect. The results suggest that CEOs age is a potential factor of Dynamic Capital Structure decision. The findings also highlight the failure of older CEOs in maximising the benefits of debt interest tax shield which prompts higher financial costs and lower firm value. The practical implication of our study lies on the need to attentively look at the CEOs age while hiring a qualified CEO that could improve the firms’ performance.